The Influence of Hamstring Length on the Flexion-relaxation Phenomenon in Relation to the Erector Spinae Muscle During Trunk Flexion - Na-hee Kim; Bo-ram Choi (Physical Therapy Korea, 2020)
Background: The flexion-relaxation phenomenon (FRP) refers to a sudden onset of activity in the erector spinae muscles that recedes or fades during full forward flexion of the trunk. Lumbar spine and hip flexion are associated with many daily physical activities that also impact trunk flexion. Shorter hamstring muscles result in a reduction of pelvic mobility that eventually culminates in low back pain (LBP). Many studies have explored the FRP in relation to LBP. However, few studies have investigated the influence of hamstring muscle length on the FRP in relation to the erector spinae muscles during trunk flexion. Objects: This study aimed to investigate the influence of hamstring muscle length on the FRP in relation to the erector spinae muscles during trunk flexion. Methods: Thirty subjects were divided into three groups according to hamstring length measured through an active knee extension test. The 30 participants consisted of 10 subjects who had a popliteal angle of 20˚ or less (Group 1), 10 subjects who had a popliteal angle of 21˚–39˚ (Group 2), and 10 subjects who had a popliteal angle of 40˚ or more (Group 3). A one-way analysis of variance was used to compare the difference in muscle activity of the erector spinae muscles during trunk flexion. Results: The subjects with a shorter hamstring length had significantly higher muscle activity in their erector spinae muscles during trunk flexion and full trunk flexion (p < 0.05). The subjects with a shorter hamstring length also had a significantly higher flexion-relaxation ratio (p < 0.05). Conclusion: The results of this study demonstrate that differences in hamstring muscle length can influence the FRP in relation to the erector spinae muscles. This finding suggests that the shortening of the hamstring might be associated with LBP.